Issues regarding the Malaysian construction industry - Hasan, Hamzah (2008)
Issues affecting the Malaysian construction industry are not only multifarious but also complex. To remain focus this paper will discuss issues pertaining to the construction industry in the context of its development, the raison d’etre of the Construction Industry Development Board (CIDB) when established by parliamentary statute in 1994. CIDB began operations in earnest beginning 1996. The need to establish a statutory body to manage development of the construction industry was mooted in the wake of numerous accidents and quality deficiencies in the construction industry, amongst which included the infamous collapse of the Highland Towers, the landslide at Gua Tempurung, and the many grouses voiced by a large segment of dissatisfied final-purchasers of the construction industry product.